DETERMINASI FAKTOR MEMPENGARUHI KINERJA PEMASARAN AYAM BROILER DI KOTA MAKASSAR - Sahabuddin, Romansyah; Muhammad, A. Fadel; Sukiman, Sukiman; Arimbawa, Arya P.; Ripal, Tyta; Goeliling, Ardhi (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to investigate the interconnectedness between entrepreneurial orientation and knowledge competence and their impact on the capabilities and marketing performance of Broiler meat chicken in Makassar, Indonesia. It employs an explanatory research design, aiming to elucidate the causal relationship between variables through hypothesis testing. The study's sample comprises 200 poultry entrepreneurs in Makassar, making it a comprehensive exploration of the local Broiler meat chicken industry. The research employs structural equation modeling (SEM) using LISREL version 8.80 as the analytical tool, enabling a rigorous analysis of the data. The findings reveal a significant and positive influence of both entrepreneurial orientation and knowledge competence on the capabilities and marketing performance of Broiler meat chicken in Makassar. This influence is evident both when considering these variables individually (partially) and when analyzed together (simultaneously). These results emphasize the significance of entrepreneurial orientation and knowledge competence in enhancing the marketing capabilities and overall performance of the Broiler meat chicken industry in the Makassar region. This research carries valuable implications for entrepreneurs, industry stakeholders, and policymakers, offering insights that can inform strategies to further improve marketing outcomes and overall performance in the Broiler meat chicken sector in the area.